The higher reading interest of pregnant mother improves the utilization of MCH book - Intan Mutiara Putri; Apriliana Apriliana; Suyani Suyani; Istri Utami (International Journal of Health Science and Technology, 2019)
The utilization of MCH book could be defined to be an activity when a mother and her close relatives actively participate in reading, learning, comprehending the contents of MCH book, and implementing it in daily routine. This research aims to discover the correlation between the reading interest of pregnant mothers and the use of MCH book. This study has been approved by the research ethics committee of Yogyakarta ‘Aisyiyah University. This cross-sectional research was performed at the Community Health Centre of Mlati II Sleman Yogyakarta. Seventy-four pregnant mothers who owned MCH book were derived from incidental sampling technic. The retrieval of primary data used questioner method. The result of chi-square test states that pregnant mothers with higher reading interest will be utilizing the MCH book four times more effective compared to those with lower interest in reading (p-value: 0,005 and 95% CI: 1,488-10,902).